Analysis of Human Rights Protection in Defamation Charges Based on Indonesian Laws (Case Study Number: 560/PDT.G/202/PN JKT.PST) - Dhani Samantha; Ika achmawati Sukarno Putri; Nasywa Laffaiza; Muhammad Raihan Hakim; Raja Drajat Hasiholan (LEGAL BRIEF, 2022)
Indonesia is a country that has a forum to voice or give opinions stipulated in the laws. However, the more freedom in giving opinions, people sometimes forget to filter what must be informed and not. In this situation, there is a defamation accusation case that won by Dr. Richard Lee. This study had reviewed the nature of defamation charges and the laws involved in it. Based on this background, this study used legal research with legislative and comparative approaches. This study examined legal norms and practices in Indonesia. It was a descriptive study which aimed to get a complete analysis and conclusion on the matter. Data collection used secondary data which includes literature study. The conclusion obtained about defamation law is through ITE Law and 310 Indonesian Criminal Codes which in this case, the law on defamation can be civil and criminal laws depending on the context of the losses made by the perpetrator.